Efektivitas Kebijakan Insentif Pajak Penghasilan Pasal 21 Di Kantor Pelayanan Pajak Pratama Jakarta Cakung Tahun 2021 - Ega Zuhendra; Notika Rahmi (Jurnal Ilmu Administrasi Publik, 2023)
The outbreak of the Covid 19 Virus which has impact on the world economy is no exeption and also has an impact on our country, which is increasingly worrying about the economy sector, March to April are very important months for taxation in Indonesia. It is hoped that the Government’s policy through this Income Tax Incentive will provide a solution for the government in overcoming the problematic impact of the Covid 19 Virus outbreaks on the economy in Indonesia The phenomenon of the problem in this study is that there are still taxpayers who are not aware of the PPh 21 incentive policy, lack of socialization regarding the applicable policies by the Director General of Taxes, and taxpayers who are aware of this incentive policy but do not understand the terms and conditions. This study aims to analyze and determine the effectiveness of PPh 21 incentive policies. In this study, Oberthur and Groen’s concept was used to explore the research results. This research uses a descriptive qualitative method by Conducting Interviews, Field Observations, and Documentation. The research location is at the Cakung Jakarta Primary Tax Service Office. The results of this study state that the effectiveness of the PPh 21 incentive policy has been implemented quite well, but there are in the form of a lack of intense socialization, a lack of understanding from the public about PPh 21 policies, and from the Tax Service Office, there are periodic system maintenance problems.